Pesticidal activity of virginiamycins S1 and M1 - Prikrylová, V; Samoukina, G V; Kandybin, N V; Ujhelyiová, L; Varkonda, S (Folia microbiologica, 1992)
Virginiamycins S1 and M1, two major components of the antibacterial antibiotic complex produced by Streptomyces virginiae and used as an animal growth promoter in animal husbandry, exhibited a selective insecticidal activity against Leptinotarsa decemlineata comparable with the effect of the organophosphorus pesticide Metathion. An acaricidal effect of the two compounds on eggs of Tetranychus urticae was also observed.
Keywords: Acari; virginiamycin; ovum; Animals; preklinické hodnocení léčiv; Female; zvířata; Larva; Ovum; hmyz; Insecticides; Insecta; Virginiamycin; Drug Evaluation, Preclinical; ženské pohlaví; insekticidy; larva